Metastable states in antihydrogen formation - Dirk van der Werf (Hyperfine Interactions, 2014)
Formation of antihydrogen atoms from antiprotons immersed in a positron plasma is simulated. Special attention is devoted to the role of metastable states, arising from the near conservation of the energy stored in the cyclotron motion of the positrons. We find that the decay of such states changes the density scaling of the formation rate.